2017
DOI: 10.1093/jjco/hyx009
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is a novel poor prognostic factor in male patients with pathological Stage I non-small cell lung cancer

Abstract: Objectives: Sarcopenia is the progressive loss of muscle mass and strength, and has a risk of adverse outcomes such as disability, poor quality of life and death. As prognosis depends not only on disease aggressiveness, but also on a patient's physical condition, sarcopenia can predict survival in patients with various cancer types. However, its effects on postoperative prognosis in patients with localized non-small cell lung cancers (NSCLC) have never been reported. Methods: We retrospectively investigated 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 23 publications
2
43
0
3
Order By: Relevance
“…In hepatopancreatobiliary cancer, low SMM is associated with reduced OS . In patients with resectable early stage non‐small‐cell lung cancer, low SMM is associated with poor short‐term and long‐term outcomes after surgery . Low SMM has also been associated with prolonged hospital stay and increased health care‐related costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatopancreatobiliary cancer, low SMM is associated with reduced OS . In patients with resectable early stage non‐small‐cell lung cancer, low SMM is associated with poor short‐term and long‐term outcomes after surgery . Low SMM has also been associated with prolonged hospital stay and increased health care‐related costs.…”
Section: Discussionmentioning
confidence: 99%
“…14 In patients with resectable early stage non-small-cell lung cancer, low SMM is associated with poor short-term and long-term outcomes after surgery. 27,28 Low SMM has also been associated with prolonged hospital stay and increased health care-related costs. A recent study in 452 patients undergoing abdominal surgery for cancer of the alimentary tract showed that patients with low SMM had a significantly longer hospital stay and significantly higher hospital costs than patients with normal SMM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that sarcopenia was associated with poor prognosis in lung cancer, but most of these included patients with advanced stage cancer . According to a rare report about sarcopenia in stage I NSCLC patients, sarcopenia was associated with poor prognosis in men but was not associated with postoperative complications . Another report, which defined sarcopenia using the erector spinae and pectoralis muscles, suggested that sarcopenia was not associated with the overall complication rate after lobectomies (mostly performed using the VATS approach) .…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al examined 90 consecutive patients undergoing lung resection for stage I NSCLC, and using L3MI to assess for sarcopenia, found that sarcopenia was an independent prognostic factor for survival as patient with a low muscle mass had a significant decrease in 5-year overall survival (20). Tsukioka et al reported on 215 male patients with pathological stage I NSCLC, and used a calculated L3MI derived from an equation using BSA to define sarcopenia; in their report, sarcopenia did not affect short-term outcomes, but was associated with a shorter median overall survival (21).…”
Section: Discussionmentioning
confidence: 99%
“…CT imaging has been found to correlate well with other methods of evaluating muscle mass, which is useful as CT imaging is routinely done prior to resection (19). In lung cancer, recent studies have found evidence that sarcopenia is an independent risk factor for decreased overall survival (20,21). In those studies, assessment of muscle mass was done at the level of L3, which sometimes necessitates a CT scan lower than routinely performed to evaluate chest pathology.…”
Section: Introductionmentioning
confidence: 99%